Ekonomski vidiki ekscesne cene - Ferčič, Aleš (LeXonomica, 2021)
Economic aspects of excessive priceIn this article, the author deals with the fundamental economic aspects of an excessive price or excessive pricing within the context of article 102 TFEU. In this regard, he considers the relevant practice of the European Commission, of the Court of Justice of the European Union, and of the Office of fair trading. The main emphasis is on the methodology used in order to assess the economic value of a product in question and its practical application. In this regard, the author values the main stream (frame) doctrine as defined by the Court in the United Brands case. In addition, he offers guidance for its application in individual cases. By doing so, he also identifies typical errors which can be made in case of generalization or ignorance of relevant circumstances of each particular case. Last but not least, the author also values a real meaning of the “cost+” approach and the “value for a buyer”.Ekonomski vidiki ekscesne ceneV prispevku avtor obravnava temeljne ekonomske vidike ekscesne cene v kontekstu člena 102 PDEU, pri čemer upošteva prakso Evropske komisije, Sodišča Evropske unije in angleškega varuha konkurence. Poudarek je na metodologiji za presojo ekonomske vrednosti opazovanega produkta in njena praktična realizacija. Avtor v tej zvezi ovrednoti prevladujočo (okvirno) formulo, kakor je bila določena v zadevi United Brands, ter ponudi izhodišča za njeno ustrezno uporabo v posamičnih primerih. Pri tem opozori na tipične napake, do katerih lahko pride zaradi posploševanja ali neupoštevanja vsakokratnih relevantnih okoliščin primera, prav tako pa se opredeli do t. i. pristopa »stroški+« in »vrednost za kupca«.